Effects of growth hormone plus gonadotropins on controlled ovarian stimulation in infertile women of advanced age, poor responders, and previous in vitro fertilization failure patients - Yao-Kai Ho; Tsung-Hsien Lee; Chun-I. Lee; En-Hui Cheng; Chun-Chia Huang; Lii-Shung Huang; Maw-Sheng Lee (Elsevier, 2017)
Objective: To investigate the effects of growth hormone (GH) cotreatment in ovarian stimulation in infertile women of advanced age, poor responders, and patients with one or more previous IVF treatment failures. Materials and methods: We conducted a retrospective observational study of 436 patients undergoing GH cotreatment in ovarian stimulation. The first arm included 134 infertile women of advanced age. The second arm included 236 patients with one or more IVF previous treatment failures, and the third arm included 66 younger poor responders. Main outcome measures were the number of oocytes and embryos, quality of embryos, and implantation and pregnancy rates. Results: In infertile women of advanced age, GH plus ovarian stimulation yielded no statistical differences in the numbers of oocytes and embryos, quality of embryo, and rates of implantation and pregnancy. In the second arm, the mature oocyte number (8.2 vs. 6.8), implantation rate (16.1% vs. 0%), and pregnancy rate (33.9% vs. 0%) in the GH cotreatment group differed significantly from those in the control group; the rate of good-quality embryos in the GH cotreatment group improved from 35.5% ± 31.1%-41.4% ± 30.6% in this arm. Similar results were observed in the third arm; in this arm, the clinical pregnancy rate was 30.3% in the GH cotreatment group and 6.1% in the control group. Conclusion: No significant differences were observed in infertile women of advanced age, which may be due to the low GH dose. The GH adjuvant therapy for patients with one or more previous IVF treatment failures and for poor responders significantly improved the oocyte and embryo numbers as well as implantation and pregnancy rates.